Integrating Sharia values and green jobs: A socio-economic model for the Indonesia’s halal industry - Nur Apriliani Bahri; Muhammad Gilang; Neti Hekawati (Privietlab, 2026)
This study aims to develop a socio-economic model of green jobs in Indonesia's halal industry by examining the interrelationships among Sharia values, sustainable development principles, and green employment through qualitative content analysis. The study employed a qualitative research design using documentary analysis of national strategic policy documents, corporate sustainability reports, government publications, international institutional reports, and relevant scientific literature. The collected documents were analyzed through a systematic process of coding, categorization, and thematic interpretation to identify recurring concepts and conceptual relationships related to the halal industry, sustainability, and green jobs. The findings reveal that the principles of maqashid sharia, particularly hifz al-bi'ah (environmental protection) and hifz al-mal (protection of wealth), provide an ethical foundation for integrating environmental sustainability with socio-economic development in the halal industry. Four major themes emerged from the analysis: the integration of Sharia values into sustainability and green jobs, strengthening human resources for the green economy, the role of industry in promoting sustainable business practices, and the development of a halal ecosystem through renewable energy and socio-ecological justice. These themes were synthesized into a socio-economic model that illustrates the interaction of spiritual, social, and ecological dimensions in supporting green job creation within the halal industry. The study concludes that strengthening cross-sector collaboration among government, industry, educational institutions, and other stakeholders is essential to developing a halal industry that is competitive, environmentally responsible, and aligned with Sustainable Development Goals (SDG). Keywords: green jobs; halal industry; maqashid sharia; qualitative content analysis; sustainable development.